2001
DOI: 10.1029/2000jd000184
|View full text |Cite
|
Sign up to set email alerts
|

Radiance and Jacobian intercomparison of radiative transfer models applied to HIRS and AMSU channels

Abstract: Abstract. The goals of this study are the evaluation of current fast radiative transfer models (RTMs) and line-by-line (LBL) models. The intercomparison focuses on the modeling of 11 representative sounding channels routinely used at numerical weather prediction centers: 7 HIRS (High-resolution Infrared Sounder) and 4 AMSU (advanced microwave sounding unit) channels. Interest in this topic was evident by the participation of 24 scientists from 16 institutions. An ensemble of 42 diverse atmospheres was used and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
112
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(119 citation statements)
references
References 30 publications
3
112
1
Order By: Relevance
“…The bias found for AMSU channel 18 was 0.37 K compared to the reference model of the study by Garand et al [2001]. Bias here means the mean (over a set of atmospheric states) of the difference between brightness temperatures from ARTS and from the reference model, and the criteria for the quality of the agreement are the ones stated in the latter study.…”
Section: A1 Atmospheric Radiative Transfer Simulator (Arts)mentioning
confidence: 69%
See 3 more Smart Citations
“…The bias found for AMSU channel 18 was 0.37 K compared to the reference model of the study by Garand et al [2001]. Bias here means the mean (over a set of atmospheric states) of the difference between brightness temperatures from ARTS and from the reference model, and the criteria for the quality of the agreement are the ones stated in the latter study.…”
Section: A1 Atmospheric Radiative Transfer Simulator (Arts)mentioning
confidence: 69%
“…[111] Note that in an independent exercise [John et al, 2002], ARTS was found to be in very good agreement with a large group of operational radiative transfer models for this sensor type which have been compared in the work of Garand et al [2001]. The bias found for AMSU channel 18 was 0.37 K compared to the reference model of the study by Garand et al [2001].…”
Section: A1 Atmospheric Radiative Transfer Simulator (Arts)mentioning
confidence: 77%
See 2 more Smart Citations
“…This can be done analytically or by numerically estimating the Jacobian using finite differences by applying small perturbations to the background state as input to the nonlinear operator. This perturbation method has been applied previously to radiative transfer (Chevallier and Mahfouf, 2001;Garand et al, 2001) and cloud models (Fillion and Mahfouf, 2003) for the sensitivity characterization of parametrization schemes. Rüdiger et al (2010) have also tested this approach for the assimilation of remotely sensed observations of vegetation biomass into a land surface model.…”
Section: Tangent Linear and Adjoint Operatorsmentioning
confidence: 99%